Feminist social work pedagogy: personal, cultural and structural advocacy in the academy. Issue 3 (3rd April 2021) - Hosken, Norah; Vassos, Sevi; Epstein, Sarah
ABSTRACT: The principles of social justice underpin the various professional standards that guide social work practice in Australia and internationally. Although the work of practising social workers is explicitly guided by these principles, little is currently known about how social work academics enact these principles in their pedagogical practice and administrative work within the neoliberal academy. As a response to the managerial ethos of the university, the authors developed a feminist collaborative, research, teaching and advocacy centre called Critical Edge Women (CrEW). Drawing on the literature and our own reflections as feminist social work academics, CrEW interrogates the processes and tensions experienced in trying to embody a socially just pedagogy and practice in a social work program. We report on what has been trialled over the past two years. In this article, the connection between the administration role of social work academics and feminist social work pedagogy is foregrounded. An introductory framework is offered outlining principles of a feminist social work lens for socially just pedagogy and practice. Although focused on an Australian context, the pedagogical processes and advocacy practices discussed have implications for feminist pedagogies more broadly in higher education, and for social work practice in organisations.